On the actuality entailment of Spanish root modals - Carrasco, Angeles (Borealis – An International Journal of Hispanic Linguistics, 2019)
This paper examines the actuality entailments of Spanish past perfective root modals. I wil side with those authors that maintain that the phenomenon is syntactic. Nevertheless, the emphasis will not be on scope differences between projections, but on the fact that the root modal periphrasis is an example of restructuring structure. More precisely, I will claim that root modal periphrases may be included among the constructions with a low level of restructuring. This point of view will take me to propose that these periphrastic structures give rise to a complex event which behaves as a non-homogeneous predicate with regard to temporal-aspectual meaning.